The Organotin Applications in Biological, Industrial and Agricultural Sectors: A Systematic Review - Abdualbasit M. Graisa; Amani A. Husain; Mohammed H. Al-Mashhadani; Dina S. Ahmed; Hadeel Adil; Emad Yousif (Fakultas Teknik, 2022)
In the last few decades, the chemistry of organotin (IV) complexes of many biologically important compounds, has received significant interest in the preparation, identification and application of organotin units which are employed as photo-stabilizers, pesticides, pharmaceuticals and fire retardants. Biological properties of the system are modified by changing the organic ligands in organotin(IV) complexes. Using organotin (IV) materials in medications has brought significant attention by researchers recently. This is due to these compounds have demonstrated an excellent biological activity as well as organotin (IV) compounds are considers as anti-oxidant molecules as they work free radical scavengers. On the other hand, organotin (IV) complexes were used as photo-stabilizers for different types of plastic polymers. In this paper will review the most important potential work using organotin (IV) in both medicine and industrial applications.